Clinical imaging factors of excellent outcome after thrombolysis in large-vessel stroke: a THRACE subgroup analysis. Issue 4 (8th June 2021) - Riou-Comte, Nolwenn; Gory, Benjamin; Soudant, Marc; Zhu, François; Xie, Yu; Humbertjean, Lisa; Mione, Gioia; Oppenheim, Catherine; Guillemin, Francis; Bracard, Serge; Richard, Sébastien
Abstract : Background: For patients with stroke with large-vessel occlusion (LVO), study of factors predicting response to intravenous thrombolysis (IVT) would allow identifying subgroups with high expected gain, and those for whom it could be considered as futile, and even detrimental. From patients included in the Mechanical Thrombectomy After Intravenous Alteplase vs Alteplase Alone After Stroke trial, we investigated clinical-imaging factors associated with optimal response to IVT. Methods: We included patients receiving IVT alone. Excellent outcome was defined by a 3-month modified Rankin Scale (mRS) score ≤1. Clinical-imaging predictors were assessed on multivariate analysis after multiple imputations. The predictive performance of the model was assessed with the C-statistic. Results: Among 247 patients with LVO treated with IVT alone, 77 (31%) showed 3-month mRS ≤1. Predictors of 3-month mRS ≤1 were no medical history of hypertension (OR 2.43; 95% CI 1.74 to 3.38; p=0.007); no current smoking (OR 2.76; 95% CI 1.79 to 4.26; p=0.02); onset-to-IVT time (OR 0.47 per hour increase; 95% CI 0.23 to 0.78; p=0.003); diffusion-weighted imaging (DWI) volume (OR 0.78 per 10 mL increase; 95% CI 0.68 to 0.89; p=0.0004); presence of susceptibility vessel sign (SVS) (OR 7.89; 95% CI 1.65 to 37.78; p=0.01) and SVS length (OR 0.87 per mm increase; 95% CI 0.80 to 0.94; p=0.001). The prediction models showed a C-statistic=0.79 (95% CI 0.79 to 0.80). Conclusions: In patients with stroke with anterior-circulation LVO treated with IVT alone, predictors of excellent outcome at 3 months were no medical history of hypertension or current smoking, reduced onset-to-IVT time, small DWI volume, presence of SVS and short SVS length. These predictive factors could help practitioners in decision-making for IVT implementation in reperfusion strategies, all the more for the drip and ship paradigm. Trial registration number: NCT01062698 .